Development and Characterization of a Clotrimazole–Zinc Oxide Topical Suspension with Improved Skin Protection - P. Honmane, Pravin; Patil, Swati; Hadadare, Manojkumar; Londhe, Supriya (Journal of Neonatal Surgery, 2025)
Clotrimazole is a well-known antifungal agent frequently used in the treatment of various superficial fungal infections, while Zinc Oxide is a widely accepted skin protectant with soothing, astringent, and antimicrobial properties. Combining these agents in a topical suspension offers a dual therapeutic approach, enhancing both antifungal efficacy and skin protection. The present study aimed to formulate, evaluate, and conduct stability studies on topical suspensions containing Clotrimazole and Zinc Oxide to enhance skin protective properties while maintaining effective antifungal activity. Four topical suspension formulations (F1–F4) were developed by varying the concentration of suspending agents and were assessed for organoleptic characteristics, pH, viscosity, spreadability, drug content, and in vitro antifungal activity against Candida albicans. Viscosity was determined using a Brookfield viscometer, drug content was analyzed by UV–Visible spectrophotometry at 261 nm, and pH was measured using a calibrated digital pH meter. The agar well diffusion method was employed to assess antifungal activity, while stability studies were carried out as per ICH Q1A(R2) guidelines under real-time and accelerated conditions for three months. All formulations showed acceptable organoleptic properties and pH values suitable for topical use, with formulation F3 exhibiting optimum viscosity, satisfactory spreadability, the highest drug content (99.4%), and superior antifungal activity (22.0 mm zone of inhibition). Stability studies confirmed no significant changes in evaluated parameters over the study period. Overall, the optimized formulation F3 demonstrated enhanced antifungal efficacy and skin protective properties, suggesting its potential as a safe and effective topical treatment for fungal skin infections.